2001
DOI: 10.1046/j.1463-1318.2001.00223.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of surgeon organization and specialization in rectal cancer outcome

Abstract: Specialization and centralization influence the quality of rectal cancer surgery, mainly local recurrence rates and survival after low anterior resection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
27
0
7

Year Published

2006
2006
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(34 citation statements)
references
References 24 publications
0
27
0
7
Order By: Relevance
“…Nevertheless, there has been a trend in the past few decades, especially in tertiary referral hospitals, to organize clinical units of surgeons with a special interest in and professional activity focused specifically on coloproctology. Several studies 11,12 have shown improved outcomes from fully trained colorectal surgeons (CSs). However, surgeon-related factors and outcomes have mostly been studied in the elective-surgery scenario of colorectal cancer, showing differences in terms of curative resection rate, local recurrence, and survival that reflect the degree of specialization.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, there has been a trend in the past few decades, especially in tertiary referral hospitals, to organize clinical units of surgeons with a special interest in and professional activity focused specifically on coloproctology. Several studies 11,12 have shown improved outcomes from fully trained colorectal surgeons (CSs). However, surgeon-related factors and outcomes have mostly been studied in the elective-surgery scenario of colorectal cancer, showing differences in terms of curative resection rate, local recurrence, and survival that reflect the degree of specialization.…”
mentioning
confidence: 99%
“…However, surgeon-related factors and outcomes have mostly been studied in the elective-surgery scenario of colorectal cancer, showing differences in terms of curative resection rate, local recurrence, and survival that reflect the degree of specialization. 12,13 It has also been observed that specialization in colon and rectal surgery may contribute to the improvement of outcomes in the elective management of fistula-complicating diverticulitis. 4 Nevertheless, limited conclusions can be drawn from the literature concerning the role of specialization with regard to outcomes in acute colonic emergencies because it has been studied only in 1 series dealing with patients with leftsided colorectal cancer and diverticulitis.…”
mentioning
confidence: 99%
“…Several studies reported increasing or stable rates of surgery for both colon and rectal cancers over time (27,30,32,36,66,68,79). However, three studies contrasted decreasing trends for abdominoperineal resection (APR) with increasing trends sphincter-sparing surgery (27,83,86). Additionally, a small number of studies compared trends over time to the implementation of guidelines or national consensus statements (32,46,49,52,66,74).…”
Section: Initial Treatmentmentioning
confidence: 99%
“…Por outro lado, juntou-se o aprimoramento do cirurgião, do mais refinado senso relacionado à estesia, ao apuro da habilidade manual e à criação de técnicas cirúrgicas mais apropriadas ao segmento retal, facultando a máxima preservação, a mínima mutilação e a mais integral manutenção da função sem os prejuízos dos objetivos oncológicos como fator prognóstico de tratamento do câncer de reto [9][10][11][12][13][14][15][16] .…”
Section: Rev Bras Coloproct Janeiro/março 2009unclassified